Od mitu zdegradowanego do zielonego misterium w?twórczości Bolesława Leśmiana = From degraded myth to green mystery in the works of Bolesław Leśmian - Wawryk, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The findings of the myth researchers are useful in the study of Bolesław Leśmian`s works. Thepresence of myth in his works has already been noticed by scholars. In this context, not enoughattention has been paid to "Klechdy sezamowe" ("Sesame Tales") and "Przygody Sindbada Żeglarza"("Adventures of Sindbad the Sailor"). These fairy tales for children can be interpreted as a degradedmyth. They contain a number of elements which develop or transform in other poet`s works. A fairytale picture is reflected in a poetic counterpart, which in turn refers to a mythical structure. Inpoetry myth regains its primordial functions and refers to the realm of the sacred.
Keywords: Leśmian, Bolesław (1877-1937); Poezja polska - 19-20 w.; mit; baśń